Plant tissue culture and biotecnology - Rao,P Madhusudan; Abdin, Malik Zainul; Ali, Athar; Kamaluddin; Kiran, Usha. (NewDeli: block prints, 2013)
The book traces the roots of plant biotechnology from the basic sciences to current applications in the biological and agricultural sciences, industry, and medicine. Providing intriguing opportunities to manipulate plant genetic and metabolic systems, plant biotechnology has now become an exciting area of research. The book vividly describes the processes and methods used to genetically engineer plants for agricultural, environmental and industrial purposes, while also discussing related bioethical and biosafety issues. It also highlights important factors that are often overlooked by methodologies used to develop plants' tolerance against biotic and abiotic stresses and in the development of special foods, bio-chemicals, and pharmaceuticals. The topics discussed will be of considerable interest to both graduate and postgraduate students. Further, the book offers an ideal reference guide for teachers and researcher alike, bridging the gap between fundamental and advanced approaches.
Chapter 1. Historical Perspective and Basics Principles of Plant Tissue Culture (Anwar Shahzad) -- Chapter 2. Plant Tissue Culture: Applications in Plant Improvement and Conservation (Anwar Shahzad) -- Chapter 3. Plant Genetic Resources: Their Conservation and Utility for Plant Improvement (Tapan Kumar Mondal) -- Chapter 4. Methods in Transgenic Technology (Malik Z. Abdin) -- Chapter 5. Plant Promoters - Characterization and Applications in Transgenic Technology (R Srinivasan) -- Chapter 6. Metabolic Engineering of Secondary Plant Metabolism (Malik Z. Abdin) -- Chapter 7. Plastome Engineering: Basics Principles and Applications (Shashi Kumar) -- Chapter 8. Genetic Engineering to improve biotic stress tolerance in plants (Praveen Kumar Verma) -- Chapter 9. Developing stress tolerant plants by manipulating components involved in oxidative stress (Shweta Sharma) -- Chapter 10. Plant Adaptation in Mountain Ecosystem (Sanjay Kumar) -- Chapter 11. Drought-associated micro RNAs in Plants: Characterization and Functions (Z. Abdin) -- Chapter 12. Molecular Markers and Marker Assisted Selection in Crop Plants (M.A. Kamaluddin) -- Chapter 13. Plant-Based Edible Vaccines: Issues and Advantages (M.Z. Abdin) -- Chapter 14. Biosafety, Bioethics and IPR issues in Plant Biotechnology (Usha kiran).
Description based on publisher-supplied MARC data.
Keywords: Plant tissue culture; Nucleic acids; Plant breeding; Plant genetics; Plant physiology; Plant Breeding/Biotechnology.; Nucleic Acid Chemistry; Plant Genetics and Genomics; Plant Physiology